PENGARUH PENCAMPURAN RUMPUT LAUT DENGAN POLIMER XANTHAN GUM TERHADAP VISKOSITAS DAN ADSORPSI - Valentyn Paul Bodywein Hattu; Deny Ismail Pellu (Journal Mechanical Engineering, 2024)
Polymer injection is an EOR method using a polymer solution to increase oil recovery by decreasing the oil-water mobility ratio by increasing the viscosity of the injection water. The purpose of this study was to analyze the effect of adding seaweed to xanthan gum polymer at various concentrations. The influence that is analyzed in this study is the viscosity test and the adsorption of the solution. From the research that has been carried out, it can be concluded that the best polymer viscosity is a polymer mixture of xanthan gum and seaweed, while based on the adsorption test, xanthan gum polymer is the best.. Keywords: Polymer Flooding, EOR, Viscosity, Adsorption